Cyberporn: a study of the awareness of the existing law among UiTM students / Azimah Ahmad...[et al.] - Ahmad, Azimah; Abd Malek, Khairunnisa; Shariffudin, Norashikin; Mohd Zaini, Zafran Zafri (2006)
This research is on the subject of online pornography, specifically on the awareness of the law relating to cyber pornography. This research focuses on UiTM students to enable them to be more aware of the law and will prevent them from making pornographic surfing a habit. The reason we choose students as subject matter of this research is because they are the group of people that are likely to view online pornography and internet is a favorite method for youth nowadays. While doing this research we identified the laws regarding online pornography in Malaysia and other jurisdictions, conducted an investigation of awareness of the existing law relating to cyber pornography among UiTM students and at the end of this research we came up with the recommendation of possible actions to increase such awareness among students. From the research we found that the level of awareness among the UiTM students is in critical level. There are only a few students aware the existing law relating to online pornography. Most of the students are not aware or does not care about the existing law relating to cyber pornography. Unfortunately, those who claimed to know the law has the wrong idea on what the law is. From the finding we get from this research, there should be a specific law regulating to online pornography because it can be conclude that the public are not aware and does not understand the consequences of online pornography.